The Role of Electronic Library Systems in the Development of Students’ Information Competence - S. Potapova; N. Ambrosenko; V. Novikova (Открытое образование (Москва), 2025)
The purpose of the study is to theoretically substantiate the importance of introducing electronic library systems into the educational process with an emphasis on the formation of information competence of students in higher education institutions. With the rapid digitalization of the educational environment, it becomes necessary to identify key skills that will help students effectively interact with information resources. The research aims to identify the advantages of using electronic library systems as a tool for developing critical thinking and overcoming barriers to mastering modern information technologies. The materials and research methods include the analysis of literary sources and normative documentation, which allowed us to formulate the theoretical foundations of the formation of information competence among students. The application of the competence approach contributed to the systematization of knowledge about the necessary skills of working with information. To illustrate the successful application of electronic library systems in the educational process, a case method was used, which demonstrates the practical significance of the research. A comparative analysis was also used to identify the correspondence of skills of working with electronic library systems to indicators of key competencies of students. The results show that in the era of total digitalization of the educational process, the competence approach remains an effective strategy that provides systematic monitoring and support for the development of students’ competencies at all stages of learning, starting with the formation of basic skills and ending with the achievement of professional skills. There is a growing interest in information competence among researchers and lecturers, which makes it a priority strategy for the development of educational systems. Electronic library systems at the legislative level have become integral components of the electronic information and educational environment of the university. However, their implementation in the educational process is associated with a number of difficulties that require study and overcoming for widespread use. The positive experience of introducing modular training of students to work with electronic library systems is considered. The correspondence of the skills acquired by students when working with library systems to indicators of achieving key competencies is clearly demonstrated, which confirms the positive impact of such training on the formation of information competence as a key personality trait in the era of digitalization. The conclusion emphasizes that the formation of information competence of future specialists at the training stage is a prerequisite for successful professional activity. This is consistent with the ideas of advanced education and requires a transformation of the education system. Teaching the principles of information systems through information and communication technologies in the electronic information and educational environment of the university plays an important role in this process, developing information competence and preparing students for professional activity in a digital society. Ultimately, such changes will contribute to the creation of a more flexible and competitive education system that meets the challenges of the modern era.